If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -42 = -2 Reorder the terms: -42 + 8x = -2 Solving -42 + 8x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 8x = -2 + 42 Combine like terms: -42 + 42 = 0 0 + 8x = -2 + 42 8x = -2 + 42 Combine like terms: -2 + 42 = 40 8x = 40 Divide each side by '8'. x = 5 Simplifying x = 5
| x+79+36=180 | | 1+n+4=9 | | X+7.64=25 | | 423x=89-3 | | 7(3.14x)= | | 7pieX= | | x^2+y^2-4y=1 | | -(-8-4)=a | | 10-2=8-3x | | -2y+16=20 | | 4b-4=2b+14 | | -0.084x^2+0.839x+5=0 | | 6(3+2a)=42 | | sin^2(4x)+2*sin(4x)*cos(4x)+cos^2(4x)= | | 0.6x+0.4x-0.5x=x | | 0.5x+0.5x=x | | 3=13-2r | | x+57+x^3=x+78 | | Y=75-12.5x | | (5x+4)(x+-8)=0 | | 9-(-10)= | | 7+6y=61 | | (9-x^2)*sqrt(x-1)=0 | | 0.5y=-12+0.5y | | 5abc*b=1 | | x^2-5x+1=3 | | 3x-6=3(5*3-24*3) | | 2*sin(2x)*cos(2x)= | | W(2w-65)=920 | | 90=3x^5/3-6 | | -3x+39=6 | | -8X+9y=-8 |